Trends, constraints and opportunities of the Asian cassava sector: An assessment - Henry, Guy; Hershey, Clair H. (International Center for Tropical Agriculture, 1998)
This paper attempts to utilize past cassava production, utilization and market trends, integrated with regional macro-economic developments, together with a general summary of current cassava R&D advances, to analyze the principal cassava sector constraints and future opportunities, both at the country and regional level.